IMPLEMENTASI APLIKASI MEDIA PEMBELAJARAN CHORD DASAR PIANO & TUTORIAL PADA SDIT DAARUL HASANAH - Ahmad Rais Ruli (CAKRAWALA: JURNAL HUMANIORA BINA SARANA INFORMATIKA, 2016)
In making this application is expected to facilitate the layman inplaying and studying piano with ease without having to use immediatelyknown piano are quite expensive. Making these applications using AdobeFlash CS6, discusses the navigation structure, storyboard (storyline), togiving action script application is also made interesting because there areaudio, video, graphics and text are combined into one to be published in theform of exe, so no need there adobe flash applications in the computer orlaptop. Integrated Islamic School in essence is a school that implements theconcept of Islamic education based on the Qur'an and Sunnah. In itsapplication the school ISAM interpreted as school approaches by combiningthe implementation of public education and religious education curriculuminto a braid. Integrated Islamic school also emphasizes the integration inteaching methods so as to optimize the cognitive, affective and conative.Integrated Islamic School also incorporates education aqliyah, ruhiyah andjasaddiyah. In implementation combines the active involvement andparticipation of the learning environment ie school, home andmasyarakat.Dengan some understanding of the above one can draw anunderstanding that a comprehensive public school is a school of IslamicISAM organized by combining integrative values and Islamic teachings inthe curriculum building approaches effective learning and optimalengagement and cooperative between teachers and parents, and thecommunity to build character and student competitions. SDIT DaarulHasanah is a best top schools in Jakarta which foster the younger generationbecame the generation that berakhlaq uphold noble values of Islam are inthe mix with the general excellence in the scientific field,